An expanded nomological network of experienscape. Issue 3 (7th February 2020) - Tasci, Asli D.A.; Pizam, Abraham
Abstract : Purpose: Bitner's (1992) concept of servicescape has received widespread academic attention, resulting in many conceptual and empirical studies. By scanning the servicescape literature and other relevant concepts, Pizam and Tasci (2019) provided experienscape, an expanded version of servicescape, to be measured from different stakeholders' perspectives with a multidisciplinary approach. This paper aims to build on Pizam and Tasci's conceptualization of experienscape and expand its nomological network with other pertinent concepts related to different stakeholders with an interdisciplinary approach. Design/methodology/approach: This is a conceptual study analyzing diverse literature related to servicescape, experienscape and other related concepts and theories to provide an integrated and holistic picture of experienscape for more robust theory development. Several new relationships are synthesized for hypothesis development and testing in future research. Findings: The review of past research reveals that servicescape literature has mostly focused on outcomes for the benefit of brands and firms and missed outcomes for consumers and other stakeholders. In addition, servicescape literature lacks several critical concepts in the affective, cognitive and behavioral reaction domains, as well as moderator factors. The relevance of some theories such as branding (e.g. brand identity, personality, image, perceived quality, consumer value, brand value and self-congruity), cocreation/coproduction/codestruction, transformation, subjective happiness, subjective well-being and quality of life is completely overlooked. Research limitations/implications: Experienscape is a container of complex systems where needs, wants and expectations of multiple stakeholders are entertained, often at the same time through dynamic interactions among multiple stakeholders. Thus, a holistic understanding of experienscape requires dynamic integration of theories explaining the behavior of different stakeholders by cross-fertilizing theories through interdisciplinary research rather than unidisciplinary or multidisciplinary research conducted in separate silos. Originality/value: By adopting Pizam and Tasci's (2019) experienscape concept, this study expanded the relational network of service environment components (i.e. sensory, functional, social, natural and cultural components of experienscape) by incorporating diverse theories and concepts that explain cognitive, affective and conative reactions of different stakeholders to an experience environment. Additionally, the current study recommends attention to human-centric outcomes such as transformation, subjective well-being, subjective happiness and quality of life, which were completely overlooked in previous servicescape research.